Social Determinants of Health and Well-Being of Adolescents in Multicultural Families in South Korea: Social-Cultural and Community Influence - Shin, Jungeun; Lee, Hyeonkyeong; Choi, Eun Kyoung; Nam, Chungmo; Chae, Sun-Mi; Park, Oksik (Frontiers in Public Health, 2021)
Objectives: Adolescents in multicultural families (AMFs) are exposed to numerous stressors and face environmental vulnerability within the family, school, and community systems, which may affect their health and well-being. Concrete discussion on policies is lacking due to insufficient data on the levels of well-being of AMFs in South Korea. This study aimed to investigate social-cultural and community factors affecting their well-being. Methods: A cross-sectional study was conducted with a convenience sample of 206 AMFs (aged 13–18 years) from 16 general schools and 3 multicultural schools across 8 large cities. AMFs completed a self-administrative questionnaire assessing well-being, individual factors (acculturative stress, health behavior), social and community factors (social support, sense of community), and environmental factors (school type, economic status). Data were analyzed using structural equation modeling. Results: Social support and sense of community significantly and directly affected well-being. The economic status and type of school had an indirect effect on well-being, whereas the effect of acculturative stress was not significant. Factors significantly affecting adolescents’ well-being were social support, sense of community, economic status, and type of school. Conclusion: Addressing well-being may be the strategy leading AMFs to grow into healthy adults. These results could help educators, health professionals, and policymakers to identify ways to enhance the well-being of AMFs.